P141 Young Ambassadors Project: engaging patients attending a specialised young adult clinic. (20th April 2020) - Soares, Ines; Cotton, Caroline; Brinkley, Lorraine; Estrach, Cristina
Abstract: Background: Emerging literature has highlighted that transition to adult services is a challenging time where many young patients are lost to follow up and disengage with health services. Furthermore, developmentally appropriate healthcare improves adherence and empowers young people. This recognises the changing biopsychosocial development needs of young people and advocates for a 'young-person-friendly' service. Aintree Hospital runs a young adult clinic based on the EULAR guidelines. Attending patients suggested that their positive experience could support and improve engagement of peers ready for transition. At the same time, they raised that the existing shared clinical area did not feel tailored to them given the lack of age-appropriate literature and lack of representation in the existing displays. This feedback led the team to a review of the service with the ultimate aim to improve patient engagement and satisfaction. Methods: Using Plan-Do-Study-Act (PDSA) quality improvement methodology, a multidisciplinary healthcare team alongside a group of willing young adult patients (Young Ambassadors) identified a strategy to improve the young adult clinical area and facilitate transition peer support. Pilot funding was obtained from the Trust, with the aim to expand the methods to other specialities if successful. Results: The team worked with the Young Ambassadors and a professional media company to produce 'pop-ups' featuring photographs of our young adult patients with positive inspirational messages. These were purposefully produced as mobile units rather than static posters to increase flexibility of use. We also improved the availability of age-appropriate literature in the waiting room (e.g. literature from Arthur's Place, a magazine and social network for young adults with arthritis). Additionally, we developed a set of videos featuring three of our Young Ambassadors talking about their transition experience and how this affected their day-to-day lives. The videos will be available to patients ready to enter transition while still in children's services. We envisage that this initiative will provide a patient perspective of living with chronic conditions, empower young people to take control of their health needs and therefore increase adherence, independence and promote positive career and life goals. Lastly, through the project and focus group sessions, our patients have already started a support network for young patients with rheumatic diseases. Conclusion: Our young patients are keen to be involved in service development and wish to raise awareness of their life with chronic rheumatic diseases. We will measure the impact of our interventions through patient satisfaction questionnaires, group feedback sessions and by auditing patient attendance rates pre- and post-project. By working with our Young Ambassadors, we have successfully developed patient-led initiatives, tailored to young adult patients with the aim of improving future engagement and empowerment. Disclosures: I. Soares None. C. Cotton None. L. Brinkley None. C. Estrach None.